The effect of different solvents and number of extraction steps on the polyphenol content and antioxidant capacity of basil leaves (Ocimum basilicum L.) extracts - Złotek, Urszula (Saudi J Biol Sci, 2016)
The objectives of this study were to determine best conditions for the extraction of phenolic compounds from fresh, frozen and lyophilized basil leaves. The acetone mixtures with the highest addition of acetic acid extracted most of the phenolic compounds when fresh and freeze-dried material have been used. The three times procedure was more effective than once shaking procedure in most of the extracts obtained from fresh basil leaves – unlike the extracts derived from frozen material. Surprisingly, there were not any significant differences in the content of phenolics between the two used procedures in the case of lyophilized basil leaves used for extraction. Additionally, the positive correlation between the phenolic compounds content and antioxidant activity of the studied extracts has been noted. It is concluded that the acetone mixtures were more effective than the methanol ones for polyphenol extraction. The number of extraction steps in most of the cases was also a statistically significant factor affecting the yield of phenolic extraction as well as antioxidant potential of basil leaf extracts.